Difficulty of acute hepatitis C diagnosis in a hospitalised patient. Issue 1 (28th November 2018) - Takamizawa, Shigemasa; Yamada, Toru; Kitamura, Koichi; Hiraoka, Eiji
Abstract : The hepatitis C virus (HCV) causes acute hepatitis C and is commonly detected via HCV antibody testing. However, delayed seroconversion of HCV antibodies and non-specific symptoms may hinder the diagnosis of this disease. A 71-year-old woman developed acute hepatitis while hospitalised for back pain. An HCV antibody test was negative, and she had no risk factors for hepatitis C. She was referred to our hospital for further evaluation. The HCV antibody test was repeated 16 days after the initial test; owing to a positive result, she was diagnosed with acute hepatitis C. Several months thereafter, the HCV spontaneously cleared. When diagnosing an HCV infection, the time at which the testing is performed needs to coincide with the time at which HCV antibody seroconversion occurs. Timely diagnosis of an HCV infection allows appropriate treatment during the acute phase which may prevent disease progression to the chronic phase.